Chemical leaching from polyethylene mulching films to soil in strawberry farming - Scopetani, Costanza; Selonen, Salla; Cincinelli, Alessandra; Pellinen, Jukka (Frontiers in Environmental Science, 2023)
Mulching is a widely practiced agricultural technique able to boost crop productivity and to reduce weed growth and water evaporation. One of the most common materials used for mulching is polyethylene. Polyethylene films are known to contain phthalates, plasticizers recognized as endocrine disruptors, thus able to endanger the hormonal system. Only few data exist on the possible transfer of plasticizers from polyethylene mulching films to agricultural soil, especially in Europe, or on the potential implications for the environment and human health. In this study, we analyzed the occurrence of plasticizers such as phthalates and acetyl tributyl citrate from polyethylene mulching films and soil samples collected from strawberry fields where polyethylene films have been used. The samples were analyzed with a gas chromatograph-mass spectrometer and the results indicated that the soil exposed to polyethylene mulches contained a significantly higher concentration, compared to the control soil, of some of the most common plasticizers, including dibuthyl phthalate, benzylbutyl phthalate and acetyl tributyl citrate. These outcomes highlight the need to carry out further research to understand the potential risks that mulching practices can cause for the environment and human health.